Geochemical features and genesis of sedimentary rocks of the Trinity series (area of the Lahille island, West Antarctica) - Artemenko, G.V.; Ganozkiy, V.I.; Grechanivska, E.E.; Kanunikova, L.I.; Shvaika, I.A. (Reports of the National Academy of Sciences of Ukraine, 2020)
Sedimentary rocks of the Trinity series are observed on the Antarctic Peninsula from the northern part to the south for about 500 km. Determining their sedimentation area and formation conditions is of great importance for reconstructing the boundaries of the Gondwana supercontinent. Sedimentary rocks of the Trinity series ha ve been fully studied in the northern part of the Antarctic Peninsula and much less in the southern part of their distribution area. We studied the thickness of turbidites in the eastern part of the Lahille island. Turbidites are represented by intercalation of layers of quartz graywackes, thicknesses from the first centimeters to 30 cm and argillites, thicknesses from the first centimeters up to 15 cm. In quartz graywackes, fragments are predominantly monocrystalline, less often fragments of rocks of various shapes - angular, acute-angled, sharply irregular in shape. The size of the debris varies from 0.03 to 0.6 mm. Argillites consist of a host mass and oolite-like formations included in it, which are composed of cryptogranular minerals. A study of the mineral composition of argillite by X-ray diffraction analysis showed that the predominant minerals therein are quartz with a subordinate amount of biotite and an admixture of albite and some ore minerals. A very low degree of change in the primary sedimentary rocks of the Trinity series in the southern part of the area of their distribution — in the conditions of late catagenesis — early metagenesis according to the scale by N.V. Logvinenko and L.V. Orlova was established. In contrast to this region, sedimentary rocks of the Trinity series in the northern part of the Antarctic Peninsula are metamorphosed under the conditions of prehnite-pumpellyite, pumpellyite-actinolite and green shale facies. It has been established that, in the area of sedimentary rock demolition in the area of the Lahille island, the acidic and medium igneous rocks of the sodium composition of the crustal genesis are dominant and, in a subordinate amount, there were also basic rocks. According to the data obtained, sedimentary rocks of the Trinity series of the study area were formed in the upper part of the continental slope.